2000
DOI: 10.1039/b000478m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and gas permeation properties of an NaA zeolite membrane

Abstract: A high quality NaA zeolite membrane, which shows a H 2 /n-C 4 H 10 permselectivity of 106, has been synthesized on a seeded a-Al 2 O 3 support by a multistage synthesis method.The synthesis of zeolite membranes and their application in separation and catalysis have attracted great interest in recent years. 1,2 For gas separation, most studies have concentrated on MFI type (silicalite-1 and ZSM-5) zeolite membranes. Although high separation factors were obtained for mixtures of organic gases, 3-6 MFI zeolite me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 11 publications
1
29
1
Order By: Relevance
“…By comparing the NaA membrane synthesized by microwave heating on macroporous substrate with that by conventional hydrothermal synthesis by Aoki et al [22], the permeance of our NaA membrane was at least 7 times larger, while the H 2 /C 3 H 8 permselectivity was similar. Compared to that of multiple syntheses in gel [14], the permeance of the NaA membrane here was at least 2 times larger; the H 2 /C 3 H 8 permselectivity was not so high as we previously obtained [14], partly due to the choose of the permselectivity H 2 /C 3 H 8 here instead of H 2 /n-C 4 H 10 as before.…”
Section: Gas Permeation Property Of the Naa Zeolite Membranecontrasting
confidence: 64%
See 1 more Smart Citation
“…By comparing the NaA membrane synthesized by microwave heating on macroporous substrate with that by conventional hydrothermal synthesis by Aoki et al [22], the permeance of our NaA membrane was at least 7 times larger, while the H 2 /C 3 H 8 permselectivity was similar. Compared to that of multiple syntheses in gel [14], the permeance of the NaA membrane here was at least 2 times larger; the H 2 /C 3 H 8 permselectivity was not so high as we previously obtained [14], partly due to the choose of the permselectivity H 2 /C 3 H 8 here instead of H 2 /n-C 4 H 10 as before.…”
Section: Gas Permeation Property Of the Naa Zeolite Membranecontrasting
confidence: 64%
“…Multiple growths may improve the permselectivity and permeance if the reaction parameters are carefully controlled. Previously, we reported a NaA membrane with high permselectivity and a good permeance of 2.86 × 10 −7 mol s −1 m −2 Pa −1 by using multiple growth in gel with the aid of seeding of NaA crystals [14].…”
Section: Introductionmentioning
confidence: 99%
“…It will not only cut the equipment and operation cost off, but also be operated continuously if the zeolites can be configured into a membrane form. Since 1990s, much effort has been paid in the synthesis of zeolite membrane [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Till now, different types of zeolite membranes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although high separation factors have been obtained for these mixtures, the MFI zeolite membrane has not shown good separation performance for permanent gases or permanent gas/organic gas because of the large pore size and the hydrophobic nature of the zeolite [12][13][14][15]. Therefore, the investigation of the zeolite membranes with small pore size has attracted much attention [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The IR spectrum of the powders confirmed the XRD results. Our previous study also showed that only NaA zeolite membrane formed on a disk ceramic support by using the same synthesis condition [26]. From the SEM image (not shown), it can be seen that crystals formed on the ceramic hollow fiber support after one-stage synthesis.…”
Section: Resultsmentioning
confidence: 61%